A study of bacteriological and antibiotic susceptibility profile of urinary tract infection - Dr. Anusuya Devi D; Dr. Neelesh Naik; Dr. Veena Krishnamurthy (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Urinary tract infection (UTI) is one of the most common infection and is associated with significant morbidity in the community. Most of the UTI cases are treated empirically with broad-spectrum antibiotics which invariably results in the development of resistance. Aims andObjectives: The objective of this study was to determine the antibiotic susceptibility pattern of bacterial isolates causing UTI and to determine Extended spectrum beta Lactamase (ESBL) production in Gram negative isolates.Materials and Methods: A total of 724 urine samples were studied and bacteria identified by standard microbiological methods. Antibiotic sensitivity pattern was done by Kirby-Bauer disc diffusion method. Detection of ESBL was done as per Clinical and Laboratory Standards Institute (CLSI) guidelines.Results: Significant bacteriuria was detected in 238 (32.8%) samples. The most common pathogens isolated were Escherichia coli 148 (58.9%), Klebsiella pneumoniae 57 (22.7%) and Staphylococcus aureus 18 (7.1%) followed by Enterococcus spp 7 (2.7%), Proteus mirabilis 6 (2.4%), Citrobacter koseri 6 (2.4%), Pseudomonas aeruginosa 5(2%) and Staphylococcus saphrophyticus 4 (1.6%). ESBL production was seen in Klebsiella pneumoniae 12 (21%), followed by Escherichia coli 26 (17.5%). Most of the Gram-negative bacteria were susceptible to meropenam, piperacillin-tazobactum and nitrofurantoin.Conclusion: This study reveals that many bacteria causing UTI are multidrug resistant pathogens. This suggests that regular monitoring and modification of empirical therapy and it’s validation by culture report is required to prevent morbidity associated with this disease.